Metodologia histórico evangelizadora : pastoralizar a teologia e teologizar a pastoral - Danieli, Mateus (2021)
The present study aims to analyze the criteria of pastoral theology and Evangelizing Historical Methodology to justify their scientific value and importance to “theologize the pastoral and pastoralize the theology”. It is about verifying how the Evangelizing Historical Methodology is structured in the theological making and reference to pastoral praxis. For this, the first chapter will address the evangelizing methodology that can be assumed by different Church scenarios according to the foundations of João Batista Libânio. In a second chapter, the criteria of pastoral theology used by the Evangelizing Historical Methodology will be developed, along with the context of its emergence, biblical foundation, participatory research and the participatory method. And in the third chapter we will present the Evangelizing Historical Methodology and the challenges to “pastoralize the theology and theologize the pastoral”.